Mad Flight? The Montréal Migration of 1896 to Brazil - Zucchi, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
On 15 September 1896, 481 passengers left Montreal on the steamer Moravia, bound for the coffee plantations of São Paulo, Brazil. They had been enticed to migrate by offers of free passage, lodging and tools, and this at a time of high unemployment due to the economic crisis of the mid 1890s. The migrants ended up destitute, some of them begging in the streets of São Paulo. The British consular representatives helped the Canadian government to send back many of them, and most returned to Canada within eighteen months. This paper tries to understand why some people migrate as it were, on impulse, despite the warnings of neighbours and officials, and undertake a journey that to the eyes of others will end up in failure. It argues that the disposition of these individuals to migrate was strengthened by their lack of rootedness in their society and neighbourhoods.